Effective treatment of acid mine drainage by constructed wetland column: Coupling walnut shell and its biochar product as the substrates. (October 2022) - Chang, Junjun; Deng, Shengjiong; Li, Xuan; Li, Yutong; Chen, Jinquan; Duan, Changqun
Abstract: Acid mine drainage (AMD) can cause severe risks to the surrounding environment and ecosystems because of its high metal content and acidity and thus should be disposed of properly. In this study, a novel constructed wetland (CW) model system was established by packing a mixture of walnut shell (WS) and its biochar product as substrates to treat AMD with a pH of 4.0. Sucrose and plant straw broth (PSB) were successively supplemented as external carbon sources to fuel the bacterial sulfate reduction (BSR) process. Heavy metals in the AMD were efficiently removed in the CW column (Cu > 99 %, Cd > 97 %, Zn > 94 %, Cr > 93 % and Fe > 76 %), and the pH increased from 4.0 to 6.5 despite an unsatisfactory sulfate removal efficiency (<40 %). Among the substrates, biochar exhibited a notably higher metal retention capacity, followed by WS. The relative abundance of sulfate-reducing bacteria (SRB) in the biochar substrate was the highest, followed by that in the WS. The cooperation of organic-degrading bacteria mainly consisting of Cellulomonas, Clostridium and Bacteroides and SRB consortia was responsible for biotic AMD treatment in the CW. A mixture of organic solid waste and biochar is a preferable filler candidate for CW systems treating AMD although further evaluation of its capacity under varying conditions is required. Graphical abstract: Unlabelled Image Highlights: Walnut shell (WS) and its biochar product were filled in a CW model for AMD treatment. Heavy metals were effectively eliminated predominantly by substrate retention. Biochar substrate performed best in metal retention and supporting SRB growth. Syntrophy of organic-degrading bacteria and SRB was responsible for AMD biotreatment in the CW.